2011
DOI: 10.1007/s10464-011-9478-2
|View full text |Cite
|
Sign up to set email alerts
|

Development and Psychometric Evaluation of the Social Justice Scale (SJS)

Abstract: The study describes the development of the Social Justice Scale (SJS). Practitioners, educators, students, and other members of the community differ on their attitudes and values regarding social justice. It is important to assess, not only individuals' attitudes and values around social values, but also other constructs that might be related to social justice behaviors. The implication of Ajzen in Organizational Behavior and Human Decision Processes 50:179-211, (1991) theory of planned behavior suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
225
0
14

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(246 citation statements)
references
References 35 publications
7
225
0
14
Order By: Relevance
“…The survey included a 5-item subscale from the Social Justice Scale (Torres-Harding et al, 2012) that assesses self-efficacy to engage in social justice action (e.g., “I feel confident in my ability to talk to others about social injustices and the impact of social conditions on health and wellbeing”). Response options range from 1 ( strongly disagree ) to 5 ( strongly agree ).…”
Section: Methodsmentioning
confidence: 99%
“…The survey included a 5-item subscale from the Social Justice Scale (Torres-Harding et al, 2012) that assesses self-efficacy to engage in social justice action (e.g., “I feel confident in my ability to talk to others about social injustices and the impact of social conditions on health and wellbeing”). Response options range from 1 ( strongly disagree ) to 5 ( strongly agree ).…”
Section: Methodsmentioning
confidence: 99%
“…The primary aim of this study was to adapt SJS, developed by Torres-Harding et al (2012), into Turkish. High consistency level between SJS' English and Turkish applications showed that the scale provided linguistic equivalence.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Vera and Speight (2003) argue that solely focusing on theoretical knowledge could be important for researchers; however, allotting efforts to implementation will enable social justice to exist as a dynamic structure. Correspondingly, Torres-Harding, Siers, and Olson (2012) underline the fact that the relationship between attitudes and actions requires more applied research. Therefore, though not sufficient for now, it can be stated that in the literature there is an increasing tendency concerning implementation of the notion of social justice in studies (Bradley et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we utilize The Social Justice Scale (SJS) of planned behaviors developed by Torres-Harding, Siers, and Olson (2012) to capture and assess an individual's social attitudes and values and other constructs that might be related to social justice behaviors. Furthermore, we also assesses how "perceived behavior control" affects consumers' intended or actual behaviors either directly or indirectly.…”
Section: Introductionmentioning
confidence: 99%